Penguatan Kapasitas Diri Pekerja Migran Indonesia di Taiwan Melalui Edukasi Manajemen Stres, Adaptasi, dan Motivasi - Galih Panjalu Pramono; Dyah Purwaningrum; Mona Tiorina Manurung; Nurhidaya R; Nenden Nur Annisa; Fanniya Dyah Prameswari (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity was carried out to improve the psychosocial capacity of Indonesian Migrant Workers (PMI) in Taiwan through online education that focuses on work stress management, adaptability, and achievement motivation. The activity was carried out in collaboration with the GANAS Community Taiwan and was attended by 35 participants who are members of the community. The implementation was carried out online using Zoom Meeting, with three webinar sessions, each discussing one main topic. Evaluation was carried out to measure the increase in participants' understanding of the material presented. The results of the activity showed a fairly good increase in understanding for the topics of stress management, work adaptation, and achievement motivation. Participants also provided positive feedback on the delivery method and the relevance of the material to the situations they experienced. This activity shows that a webinar-based educational approach can be an effective strategy in increasing PMI's knowledge and awareness of the psychosocial issues they face in the country of placement. Follow-up in the form of similar activities periodically is needed to strengthen the impact and reach more migrant worker communities in the future.